Implementasi Program PUSPAGA Dalam Pencegahan Kekerasan Anak di Kota Serang - Ayudya, Gita Nova; Kandung Sapto Nugroho; Ima Maisaroh (Epistemik Press, 2024)
Children have the same rights guaranteed by the state. Fulfilling children's rights is the responsibility of local governments to improve child-friendly cities through the PUSPAGA program. But the fact is that there are still many children, especially in the city of Serang, who are still victims of violence, which is increasing every year. This research focuses on the implementation of the PUSPAGA Program in preventing child violence in Serang City and aims to find out more about the implementation of the PUSPAGA program in preventing child violence in Serang City using the A Model of Implementation theory according to Van Metter and Van Horn. This research uses descriptive qualitative research methods, then the data is analyzed based on the results of observations, interviews and documentation. The results of this research show that the implementation of the PUSPAGA Cahaya Hati Program in preventing violence against children has not been carried out optimally due to the existence of constraints and obstacles, namely the absence of counselors to provide counseling services, the absence of guidance to sub-district cadres related to the PUSPAGA Program, the facilities and infrastructure available. inadequate and there are still minimal outreach and promotional activities carried out due to limited budget funds.